Pengaruh Kompensasi Manajemen, Tingkat Utang dan Kepemilikan Institusional Terhadap Manajemen Pajak - Alifia Wahyu Syalfitri; Setianingsih (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This research aims to determine the influence of Management Compensation, Debt Levels and Institutional Ownership on Tax Management. The population of this research is the industrial sector listed on the Indonesia Stock Exchange (BEI) in 2019-2023. This research is quantitative research using financial reports as media and sample selection was carried out based on purposive sampling techniques, resulting in 13 (thirteen) companies. The analysis technique used in this research is Panel Data Analysis. Data processing in this research uses the Eviews 13 software application, with the research results showing that the influence of management compensation, debt levels and institutional ownership simultaneously influences tax management. Management Compensation influences Tax Management, Debt Level influences Tax Management, Institutional Ownership has no influence on Tax Management.